2008
DOI: 10.1002/jctb.2057
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of sodium carboxymethyl cellulose from paper sludge

Abstract: BACKGROUND: This paper describes the reuse of paper sludge, an industrial solid waste, for the preparation of sodium carboxymethyl cellulose (CMC). The process includes pretreatment, basification and etherification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The experiments showed that the highest cellulose content was obtained in run 9, the reasons for which could be that the non-cellulosic materials and mineral components were sufficiently well removed under the optimal conditions. 4 Gabriele 20 reckoned that the major parts of the substances that constitute the external cuticle were hydrolyzed, and the pectin substances bound to the fibres of cellulose were also in part deprotonated during the alkaline processing. Levels of variables were decided according to the K-values (Table 4) of the cellulose content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments showed that the highest cellulose content was obtained in run 9, the reasons for which could be that the non-cellulosic materials and mineral components were sufficiently well removed under the optimal conditions. 4 Gabriele 20 reckoned that the major parts of the substances that constitute the external cuticle were hydrolyzed, and the pectin substances bound to the fibres of cellulose were also in part deprotonated during the alkaline processing. Levels of variables were decided according to the K-values (Table 4) of the cellulose content.…”
Section: Resultsmentioning
confidence: 99%
“…The spectroscopic FT-IR data of the prepared CMC were also consistent with the structural assignments previous reported. 4,11,28 Thus, the results show that CMC can be synthesized from cotton stalk cellulose.…”
Section: Performance Analysis Of Cmcmentioning
confidence: 84%
See 1 more Smart Citation
“…Crystallinity value for methylcellulose has been reported in the literature between 30.4% and 52.6% depending on the degree of substitution and synthesizing method [33,39]. Similarly, for carboxymethylcellulose it has been reported between 18.4% and 63.0% depending on both degree of substitution and synthesizing method [31,40,41]. For corn starch Han et al [42] reported that it has A-type crystalline structure and 27.1% crystallinity.…”
Section: Evaluation Of Relative Degree Of Crystallinitymentioning
confidence: 89%
“…Many researchers reported the synthesis of CMC from cellulosic materials including sugar beet (Togrul & Arslan, 2003), banana pseudo stem (Adinugraha, Djagal W., & Haryadi;, flax short fibers (Kutsenko, Bochek, Vlasova, & Volchek, 2005), sago waste (Pushpamalar, Langford, Ahmad, & Lim, 2006), paper sludge (He, Wu, Fua, & Nia, 2009), cotton stalk (GenLin; Zhang, Zhang, Deng, & Sun, 2011), corn (Kumar Singh & Kumar Singh, 2012, bamboo shaving (Chen & Lou, 2014), water hyacinth (Saputra, Qadhayna, & Pitaloka, 2014), office waste paper (Joshi et al, 2015) and corn husk (Mondal, Yeasmin, & Rahman, 2015). Conventional synthesis of CMC is time consuming reaction.…”
Section: Introductionmentioning
confidence: 99%